The Role of Education Profession Courses in Building Student Character Values as Prospective Biology Teachers - Yusuf, Moh Ilham; Wulandari, Tabitha Sri Hartati (Journal of Biological Science and Education, 2025)
Education is the key to progress and quality development because humans can realize their full potential with education. One of the courses that discusses theory is the education profession course, which examines the concept of professional teachers. This study aims to determine the role of education profession courses in improving the character values of students as prospective biology teachers. This study uses a qualitative descriptive method. Data was collected by distributing research questionnaires containing statements about the study's title. The research sample included biology education students in 2020, 2021, 2022, and 2023 intakes, with 45 students as respondents. This study concludes that education profession courses are essential in improving students' character values. In addition, lecturers in charge of the course are also very important in guiding and being an example for students as prospective biology teachers.Keywords:  character values, students, teachers, biology